2011
DOI: 10.3758/s13415-011-0066-6
|View full text |Cite
|
Sign up to set email alerts
|

Executive function in Parkinson’s disease: contributions of the dorsal frontostriatal pathways to action and motivation

Abstract: Disruption of the dorsal frontostriatal pathways in Parkinson's disease (PD) is associated with impairments in motivation, as well as in executive function. The goal of this study was to investigate whether these impairments are related and, if so, whether the disruption of frontostriatal pathways compromises the ability to process the motivational aspects of feedback in such tasks. In Experiment 1, informative feedback improved the performance of young, healthy participants in a task-switching paradigm. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 69 publications
2
24
0
Order By: Relevance
“…Since CI was associated to frontal/attention impairments, occurrence of this phenomenon might be considered as an easily detected sign for attention defects, and might help to focus clinical and neuropsychological assessment toward frontal/attention dysfunctions in non-demented PD patients. Several studies have indeed suggested that dysexecutive/ attention defects are quite frequent in PD patients and can impair abilities essential to daily life, thus reducing independence and quality of life [5]. Moreover, dysexecutive/attention defects can contribute to precipitate difficulties in daily living activities such gait or driving [11,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since CI was associated to frontal/attention impairments, occurrence of this phenomenon might be considered as an easily detected sign for attention defects, and might help to focus clinical and neuropsychological assessment toward frontal/attention dysfunctions in non-demented PD patients. Several studies have indeed suggested that dysexecutive/ attention defects are quite frequent in PD patients and can impair abilities essential to daily life, thus reducing independence and quality of life [5]. Moreover, dysexecutive/attention defects can contribute to precipitate difficulties in daily living activities such gait or driving [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Among non-motor disorders characterizing Parkinson's disease (PD), dysexecutive/frontal dysfunctions are those most often reported in non-demented patients [5]. For this reason, the hypothesis according to which frontal dysfunctions are strongly associated with occurrence of CI would foresee this phenomenon to be frequent even among PD patients not affected by overt dementia.…”
Section: Introductionmentioning
confidence: 99%
“…It is commonly espoused that fronto-striatal dysfunction is a common mechanism that may underlie apathy [2], depression [35] and some of the cognitive deficits found in PD [36][37][38][39]. In this case, it makes sense that patients with both apathy and depression displayed the slowest motor and psychomotor speed (including verbal fluency), which are known to rely on fronto-striatal circuits [40].…”
Section: Discussionmentioning
confidence: 99%
“…In non-depressed individuals, improvements in executive function are observed after positive performance feedback (see Pessoa, 2009 for a review), irrespective of whether the feedback is monetary (Aarts et al, 2012; Gilbert & Fiez, 2004; Locke & Braver, 2008) or informative (Ravizza et al, 2012). Studies of cognitive control deficits and performance feedback in depression have been scarce, however.…”
mentioning
confidence: 99%
“…In order to assess this relationship in young university students, feedback effects were measured on a well-practiced task switching paradigm in which non-monetary feedback has been shown to improve performance (Ravizza et al, 2012). Specifically, the speed of switching between tasks improved when positive performance feedback about accuracy was presented.…”
mentioning
confidence: 99%